Sistem pemantauan tanah longsor berdasarkan laju adsorpsi air pada tanah menggunakan sensor kelembapan, kemiringan, dan suhu - Faisal Budiman; Erwin Susanto; Doan Perdana; Husneni Mukhtar; Yulius Anggoro Pamungkas; Yakobus Yulyanto Kevin (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2020)
This study examines the application of a landslide disaster monitoring system based on soil activity information that utilizes humidity, temperature, and accelerometer sensors. An artificial highland was built as the research object, and the landslide process was triggered by supplying the system with continuous artificial rainfall. The soil activities were observed through its slope movement, temperature, and moisture content, utilizing an accelerometer, temperature, and humidity sensors both in dry and wet conditions. The system could well observe the soil activities, and the obtained data could be accessed in real-time and online mode on a website. The time delay in sending the data to the server was 2 seconds. Moreover, the characteristics of soil porosity and its relevance to soil saturation level due to water pressure were studied as well. Kinetic study showed that the water adsorption to soil followed the intraparticle diffusion model with a coefficient of determination R2 0.99043. The system prototype should be used to build the information center of disaster mitigation, particularly in Indonesia.